Religion and Politics in Indonesia: The Role of Kyai in the 2024 Election, Case Study on Partai Kebangkitan Bangsa (PKB) - Muhammad Yaufi Nur Mutiullah (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2024)
This qualitative case study investigates the impact of religious leaders' authority on Indonesian society. In this case, religious leaders possess exceptional and reliable religious expertise and a significant impact on society. The Indonesian populace formerly referred to them as Kyai. This study primarily examines the impact of the Kyai on the Partai Kebangkitan Bangsa (PKB) party following the Ijtima' Ulama Nusantara gathering. This gathering serves as a strategic maneuver by PKB to secure victory in the upcoming 2024 general election. This study examines the impact of the religious leaders' authority within the PKB party leading up to the 2024 general election. The author contends that religious leaders in Indonesia wield authority that extends beyond religious matters and encompasses all aspects of Indonesian culture, including politics. The author also aims to assert that the party utilizes the influence of the kyai to enhance its electability and garner support from the community. It has been demonstrated, among other ways, through the Ijtima 'Ulama Nusantara event hosted by the PKB party to secure victory in the 2024 general election. This study utilized a descriptive-analytic methodology. This study gathered written data from multiple literary works and crucial information or news from the media. This study employed Clifford Geertz's theory on religious experts as cultural brokers.